Getting Leopards to Change their Spots: Co-creating a New Professional Role Identity - Reay, Trish; Goodrick, Elizabeth; Waldorff, Susanne Boch; Casebeer, Ann (Academy of Management Journal, 2017)
We investigated how professional role identity change can be accomplished in highly institutionalized contexts characterized by resiliency. We show that the collective professional role identity of family physicians was changed through a process of reinterpreting multiple logics and their relationships. Through our inductive analyses, we identified four mechanisms that occurred through social interactions and collectively served to rearrange the constellation of logics guiding physician role identity: (1) revealing the influence of a hidden logic; (2) reinforcing the conflict between logics; (3) reframing the meaning of a dominant logic; and (4) re-embedding the new arrangement of logics. We found that the change in physician professional role identity required significant identity work by a group of actors, but particularly by the managers who had been charged with leading the reform initiative. We contribute to the professional role identity and institutional literatures by showing how others can engage in social interactions with professionals to facilitate the reinterpretation and rearranging of institutional logics that guide collective professional role identity.